Water erosion on marl slopes and prevention of its effects using conservation of water and soil systems in the Wadi Isser watershed – Algeria - Zobiri Mohamed; Mazour Mohamed; Morsli Boutkhil (Journal of Water and Land Development, 2018)
Water erosion remains a major concern on the marly slopes. Where erosive processes continue to increase and continue to pose serious problems and where knowledge is still insufficient on erodibility and its evolution and on solutions to soil erosion problems. The aim of this work is to contribute to the understanding of the functioning of soils on marl substrate in relation to erosion and to evaluate the effectiveness of the anti-erosion measures used in this type of environment. The Isser watershed, where several anti-erosion techniques were used, is the subject of this study. The analysis of the anti-erosion installations shows that most of the developments have been made according to standards and have worked well. But their effectiveness is different from one technique to another. The earthen thresholds seem to be the most suitable and the most effective. The effectiveness of earthen structures is summed up in stability, durability, cost-effectiveness, sediment storage, flood plating and water storage for a significant length of time, and had a positive impact on reducing erosion and the silting rate of the dam. The gabion thresholds also have a better stability and a good seating, but they are very sensitive and can undergo damage that reduces their effectiveness with regard to erosion. Dry stone thresholds are the least desirable and are often inadequate and inefficient in this type of terrain. A purely mechanical and/or biological vision in this type of environment is however insufficient, the mechanical arrangements associated with the biological developments are more effective.